Implementasi Adaptasi Kebiasaan Baru dalam Pemeliharaan Wisata Siwang Paradise oleh Masyarakat Desa Urimessing Ambon - Vransisca Kissya; Johana Nahuway; Citra Oktaviana Ayuningtias (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The COVID-19 pandemic has significantly impacted various sectors of life, including tourism. To ensure the continuity of tourism activities during the pandemic and beyond, the government has promoted a new habit adaptation (AKB) policy, encompassing changes in community behavior in maintaining cleanliness, health, and environmental sustainability. This study aims to analyze the process of socializing new habit adaptations carried out by the Urimessing Village community in environmental maintenance at the Siwang Paradise tourist site, Ambon City. The method used was qualitative with data collection techniques through in-depth interviews, field observations, and documentation studies. The results indicate that AKB socialization was carried out through various communication channels such as traditional meetings, social media, and cooperation activities. The community played an active role in maintaining cleanliness, implementing health protocols, and preserving the environment as part of local tourism recovery efforts. This study recommends strengthening collaboration between the government, community organizations, and tourism awareness groups (Pokdarwis) to sustainably increase the effectiveness of socialization and implementation of AKB